PENGARUH CAR (CAPITAL ADEQUACY RATIO) DAN NIM (NET INTEREST MARGIN) TERHADAP ROA (RETURN ON ASSET) - Devi Anggraini; Niken Suryaningtias (The Asia Pacific Journal Of Management Studies, 2017)
This study aims to determine the effect of CAR (Capital Adequacy Ratio) and NIM (Net Interest Margin) Against ROA (Return On Asset) at PT. Bank Rakyat Indonesia (Persero) Tbk.The independent variables in this study are CAR (Capital Adequacy Ratio) and NIM (Net Interest Margin), while the dependent variable is ROA (Return On Asset). The data used in this study are secondary data obtained from the Annual Report per year Bank BRI, in www.bri.co.id. With the data used is an overview annual finance in the 2002-2016 observation period. Data analysis techniques in this study using descriptive statistics, classic assumption tests, multiple linear analysis and hypothesis testing. The results of this study indicate that partially (Test t) variable CAR (Capital Adequacy Ratio) does not have a significant effect on the significant ROA (Return On Assets) seen from t count < ttable (1,428 <1,771), with a significance of 0,179> 0,05 while the NIM variable (Net Interest Margin) significant effect on ROA (Return On Assets) can be seen from t Count > t table (2,388> 1,771) with significance of 0.034 <0.05. Simultaneously (Test F) variable CAR (Capital Adequacy Ratio) and NIM (Net Interest Margin) there is a significant effect seen from F count > F Table (4,158> 3,89) with a significance level of 0.042 <0.05. Keywords: CAR (Capital Adequacy Ratio), NIM (Net Interest Margin), ROA (Return On Asset)